DAYA ADAPTASI KELOMPOK TANI LESTARI DALAM KEBERLANJUTAN USAHATANI PADI DI ERA NEW NORMAL - Wahyu Rohsari Widowati; Agus Subhan Prasetyo; Joko Mariyono (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The Lestari Tani Farmers Group discovered several issues regarding their rice farming business. The problems faced in the new normal era affect the outcome and sustainability of Lestari Tani Farmers Group rice farming. The problem is overcome by implementing several forms of adaptation that aim to reduce the impact of losses and maintain the sustainability of their agriculture. This research aims to discover the problems faced and the applied forms of adaptation. It is necessary to do this research to analyze the issues faced and several states of adaptation that were implemented in the Lestari Tani Farmers Group. This research was conducted in January-March 2022 in Lestari Tani Farmers Group. The determination used in this study amounted to 25 determinants consisting of a key informant, namely the chairman of the Lestari Tani Farmer Group and the other 24 members of the farmer group determined purposively. The primary data were collected from interviews, observation, and documentation. The secondary data were collected from Lestari Tani Group and BPP Selogiri. The method of analysis in this study was Miles and Huberman Method. The issues faced by the Lestari Tani Farmer Group consisted of: a decrease in the selling price of grain and rice, a reduction in the amount of production, a scarcity of fertilizers, an increase in production costs, and labour difficulties. The adaptation forms implemented include selling wet grain to intermediaries, producing organic fertilizer, buying more non-subsidized fertilizers, and looking for workers from outside the region.